Partisipasi Politik Jemaat Ahmadiyah Dalam Pilkada 2020 (Studi Kasus Ahmadiyah Kota Mataram) - Hamid, Ihsan; Anggeraini, Juliya; Maulana, Fikri (Yayasan Alpatih Harapan Semesta, 2024)
This study aims to provide an in-depth understanding of the political participation of the Ahmadiyah community in the 2020 Mataram City Regional Election. The research questions are: What forms of political participation did the Ahmadiyah community engage in during the 2020 Mataram City Regional Election? And what are the factors that hinder and encourage their political participation? The study uses a qualitative approach with data collection techniques including interviews, observations, and documentation. Data analysis methods include data sources, data reduction, data presentation, and data verification. The findings reveal that the Ahmadiyah community participated in politics by casting their votes, rejecting money politics, and never abstaining from voting. Factors encouraging participation include the social environment, political reach, government assistance, and political awareness. Meanwhile, the hindering factors involve the community's organizational detachment from political issues and a focus on maintaining the purity of Islamic teachings, which prevents potential division and moral conflicts within society.